PENGARUH METODE MASERASI DAN SOKLETASI TERHADAP STABILITAS FISIK SEDIAAN HAIR TONIC EKSTRAK ETANOL DAUN LIDAH MERTUA (Sansevieria trifasciata P.) - Agustien, Gina Septiani; Susanti, Susanti (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2022)
Hair loss is a disorder in which the amount of hair decreases or falls out more than usual without visible thinning. Hair care requires a variety of cosmetic products such as hair conditioner, cream bath and hair tonic. Hair tonic has several advantages in optimizing efforts to prevent hair loss compared to other hair treatments. Sansevieria leaves (Sansevieria trifasciata) is a plant known as an ornamental plant. Almost all parts of the sansevieria leaves can be used, but not many know that the sansevieria leaves can be used as a hair tonic to treat hair loss. The purpose of this study was to determine the effect of maceration and soxhletation methods on the physical stability of hair tonic preparations of sansevieria leaves extract with varying concentrations of 1%, 3% and 6%. Evaluation of the preparation includes organoleptic, pH, specific gravity and viscosity tests. Physical stability tests were carried out at low temperatures (4oC) and high temperatures (40oC). The test results showed (p-value <0.05) there was no effect between maceration and soxhletation methods on the physical stability of the hair tonic preparation of sansevieria leaves extract. Keywords: Hair Tonic, Sansevieria Leaves, Maceration, Soxhletation, Physical Stability.